2018
DOI: 10.1038/s41467-018-05572-z
|View full text |Cite
|
Sign up to set email alerts
|

March1-dependent modulation of donor MHC II on CD103+ dendritic cells mitigates alloimmunity

Abstract: In transplantation, donor dendritic cells (do-DCs) initiate the alloimmune response either by direct interaction with host T cells or by transferring intact donor MHC to host DCs. However, how do-DCs can be targeted for improving allograft survival is still unclear. Here we show CD103+ DCs are the major do-DC subset involved in the acute rejection of murine skin transplants. In the absence of CD103+ do-DCs, less donor MHC-II is carried to host lymph nodes, fewer allogenic T cells are primed and allograft survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…This is because immunization studies using animal models have demonstrated capability of some heat shock proteins to confer lasting protective effects against some chronic and infectious diseases. For example, mycobacterial Hsp60 and Hsp70 were shown to induce anti-inflammatory factors such as IL-10 expression by T cells [ 67 , 102 ]. It is thus not surprising that some heat shock proteins have entered the clinical trials pipe-line against conditions such as rheumatoid arthritis and autoimmune type I diabetes [ 122 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because immunization studies using animal models have demonstrated capability of some heat shock proteins to confer lasting protective effects against some chronic and infectious diseases. For example, mycobacterial Hsp60 and Hsp70 were shown to induce anti-inflammatory factors such as IL-10 expression by T cells [ 67 , 102 ]. It is thus not surprising that some heat shock proteins have entered the clinical trials pipe-line against conditions such as rheumatoid arthritis and autoimmune type I diabetes [ 122 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the immune modulatory function of bacterial Hsp70s has been based on M. tuberculosis Hsp70 [ 101 , 102 ]. MtbHsp70 binds to CD40 receptors on human monocyte cells [ 103 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tregs are potent immune regulatory cells that upregulate MARCH1 expression in DCs by IL-10. This upregulation increases MHCII ubiquitination and reduces the surface expression of MHCII, which consequently results in impaired antigen presentation by DCs ( 20 , 23 , 24 ). WWP2 has also been shown to ubiquitinate and deplete the surface expression of mature MHCII, thereby suppressing DC-mediated T cell activation during Salmonella infection ( 28 ).…”
Section: Ubiquitination In Dc-mediated Cd4 T Cell Responsesmentioning
confidence: 99%
“…Nonetheless, in the case of purified Hsp90α, it was shown that while both this chaperone and LPS could bind to SCARF1 and lead the receptor to enter a lipid raft compartment, only exposure to LPS led to significant levels of pro-inflammatory signaling through this mechanism; Hsp90α alone, although entering the lipid raft compartment did not trigger inflammatory signaling (73). In addition, it has been shown that some prokaryotic HSP paralogs tend to be antiinflammatory in contrast to the mammalian isoforms (82). The answer to this conundrum appears to be at least partially that another key class of HSP receptors is expressed on mononuclear phagocytes-the sialic acid-binding immunoglobulin-type lectins (Siglecs) (83,84).…”
Section: Scarf1 Lox-1 and Inflammationmentioning
confidence: 99%